Autonomadism of postmodern in Russian megacities: Автономадизм постмодерна в российских мегаполисах - Shlyakov, Shlyakov (Przegląd Wschodnioeuropejski, 2019)
Nomadism in postmodern stands as a principle of diffusion, allocation of bodies on social plane, implying a disruption with any fixedness: with Homeland, Home, family, identity. This principle is based on the constant movement, changes of the body. The following strategy forms a special chronotopy: space is constructed rhysomically (astructurally, acentered with equality of all possible directions of movement), and time is read a a cyclic present or as deplyment of past-future (Chronos and Eon in the concept of G. Deleuze). With transition to postmodern not only a man became a carrier of nomadic features, but also the bodies of an objective world became nomadic. Miniaturization of objects , which is accompanied by their intellectual filling, allows them to not only dive in an act of movement, but also incite movememnt and form space for realization of their own movement. A car, which in modern performed the function of subjugation of space with speed, in postmodern changed its functionality to comfort, and seriously influenced the formation of the map of the city. In this article a phenomenon of autonomadism is explored (embodiment of nomadism as a social strategy of mobility) through automobilization of society. Theoretical basis of the study is nomadological project of Deleuze – Guattari and concept of paradygm of mobility J. Urry. Among indicators which allow to talk about autonomadism are chronotopical metamorphosis in the reading of ambient landscape of motorists and the loss of identity, which led to the occurence of a hybrid “driver – car”. The following study showed that in postmodern Russian cities – metropolis a quiescence is seen as deviation and is socially excluded, spaces of quiet ar colonized by cars, sedentary places are exiled from the city or demand high economical expenses, which makes the settled way of life unprofitable.